The Influence of Principal Transformational Leadership and Infrastructure Facilities on the Performance of Senior High School Teachers in Pangururan District, Samosir Regency - Helda Sagala; Binur Panjaitan; Hasudungan Simatupang (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to determine the influence of 1) the principal's transformational leadership on teacher performance at Senior High Schools in Pangururan District, Samosir Regency; 2) facilities and infrastructure on teacher performance at Senior High Schools in Pangururan District, Samosir Regency; and 3) the simultaneous influence of transformational leadership and facilities and infrastructure on teacher performance at Senior High Schools in Pangururan District, Samosir Regency. This study used a quantitative survey approach. The population was 82 senior high school teachers in Pangururan District, Samosir Regency. The sample was a saturated sample, representing the entire population. Data were collected using a closed questionnaire consisting of 20 items to measure variable Y (Teacher Performance), 20 items for variable X1 (Principal Transformational Leadership), and 40 items for variable X2 (Infrastructure Facilities) for a total of 80 items. Before being used on actual respondents, the instrument was first tested on 30 teachers of SMA Negeri 1, Palipi District, Samosir Regency. The results of the instrument trial showed that all questionnaire items were valid and reliable. Data analysis techniques were carried out using descriptive analysis through variable categorization and parametric statistical analysis through simple and multiple linear regression equation tests, correlation and coefficient of determination tests, t-tests, and F-tests. The results of the data analysis show that: 1) there is a positive influence of the Principal's Transformational Leadership on the performance of State Senior High School teachers in Pangururan District, Samosir Regency with a contribution of 36.6%, where the strong correlation value is 0.605 with a linear equation Y = 26.535 + 0.576X1 and t count = 6.800> t table (n-2 = 80) = 2.000; 2) there is a positive influence of Facilities and Infrastructure on the performance of State Senior High School teachers in Pangururan District, Samosir Regency with a contribution of 31.2%, where the strong correlation value is 0.558, with a linear equation Y = 23.065 + 0.361 and tcount = 6.019> ttable (n-2 = 80) = 2.000 and 3) there is a positive influence of Transformational Leadership of the Principal and Facilities and Infrastructure simultaneously on the performance of State Senior High School teachers in Pangururan District, Samosir Regency with a contribution of 47.4% where the strong correlation value is 0.689, multiple linear equation Y = 10.546 + 0.426X1 + 0.236X2 and Fcount = 35.647> Ftable (k-1, n-k; 2.80) = 3.15. Thus the research hypothesis is accepted